Development of a Learning Management System Using Google Sites in Chemistry Lessons - Zulkifli Zulkifli; Faiza Rini; Dina Ramadhanti (Researcher and Lecturer Society, 2025)
Low student learning outcomes in Chemistry at SMAN 1 V Koto Kampung Dalam, Padang Pariaman Regency, are caused by teachers' limitations in utilizing interactive digital learning media. Learning is still dominated by conventional methods, while students need attractive visual and digital media to understand abstract Chemistry concepts. This study aims to develop and test the validity, practicality, and effectiveness of a Google Sites-based Learning Management System in Chemistry learning. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 30 grade XI students selected through random sampling from a total population of 92 students. The research instruments included an expert validation sheet, a teacher and student practicality questionnaire, and a learning outcome test (pre-test–post-test). The results showed that the Google Sites-based learning management system was rated